The potential functions of ferroptosis on urinary stones: mechanisms and therapeutic implications - Yue Ran; Yue Ran; Yuhan Ma; Yuhan Ma; Yuexin Luo; Yajun Ruan; Yajun Ruan (Frontiers in Physiology)
Ferroptosis is a new type of cell death driven by iron-dependent phospholipid peroxidation, which is regulated by a variety of factors including redox homeostasis, iron metabolism, lipid metabolism, cellular metabolism, and mitochondrial function, and plays an important driving role in the development of various tissues and organ damage and diseases. Kidney stones are a common urological disease characterized by high morbidity and high recurrence rate. Currently available preventive or therapeutic treatments for kidney stones are inadequate to cope with the growing clinical demand, suffering from poor efficacy and a higher risk of postoperative complications. Accumulating experimental evidence has established mechanistic links between ferroptosis and nephrolithiasis pathogenesis, highlighting the promising potential of ferroptosis-based therapeutic strategies in kidney stone treatment. This review delves into the latest advances in ferroptosis research associated with kidney stone formation. We review the latest molecular regulatory mechanisms of ferroptosis associated with kidney stone formation from five aspects and elucidate the physiological functions and pathological roles of these pathways. In the conclusion, we critically analyze the therapeutic potential of targeting key molecular mediators within these pathways, providing strategic insights for developing novel therapeutic interventions that may overcome the limitations of conventional approaches in the future.